Does coronavirus disease-19 infection affect ovarian reserve in infertile women? A retrospective study - Serkan Kahyaoglu; Muzeyyen Gulnur Ozaksit; Inci Kahyaoglu; Ahmet Arif Filiz; Meryem Kuru Pekcan; Ece Atalay; Ozlem Moraloglu Tekin (Wolters Kluwer Medknow Publications, 2022)
Background: Previous studies have revealed menstrual changes following coronavirus disease-19 (COVID-19) disease. The potential impact of COVID-19 on female reproductive organs, ovary in particular, has not been investigated thoroughly. Aims: The aim of this study was to evaluate changes in serum levels of follicle-stimulating hormone (FSH), luteinising hormone (LH) and oestradiol (E2) following COVID-19 disease as a surrogate for the detection of ovarian vulnerability to SARS-CoV-2 infection. Settings and Design: In this retrospective study, hospital records of unexplained infertile women between 21 and 40 years old who have attended our institution's reproductive medicine unit for evaluation and/or treatment of infertility have been evaluated. Materials and Methods: Menstrual cycle day 2-5 serum follicle-stimulating hormone, luteinising hormone and E2 levels of 28 infertile women have been studied both before and after the COVID-19 disease to evaluate ovarian reserve before the ovulation induction treatment cycle. Statistical Analysis Used: The demographic characteristics and hormonal results of these 28 unexplained infertile women have been compared. The Shapiro-Wilk test has been used to evaluate the normal distribution of variables. Comparison of ovarian reserve markers which were established before and after COVID-19 infection has been performed using paired samples t-test. Results: All patients except one have shown mild COVID-19 symptoms and their infection courses have resulted in uneventful recovery. Serum FSH, LH and E2 levels of 24 (85%) and serum anti-Müllerian hormone (AMH) levels of 4 (15%) patients have been evaluated before and after COVID-19 disease is statistically similar. Conclusion: COVID-19 disease or inflammatory response of the infection itself does not seem to affect pituitary gonadotropins and ovarian hormones in infertile women based on menstrual cycle day 2-5 serum FSH, LH, E2 and AMH levels. Further studies including higher patient numbers are urgently needed to clarify the potential effects of COVID-19 disease on the gonadal function of women.